Wintering and grazing steer calves: Methods of wintering steer calves that are to be grazed a full season and sold off grass, 1951-52. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Five lots of good quality Hereford steer calves, 10 head to a lot, were used in this study. They were a part of the light end of a group of 150 steel calves originating at Marfa, Texas, and purchased for experimental purposes. They were received November 8, 1951, and started on test December 22, 1951. Until they were started on test, they were fed sorghum silage, prairie hay, and 1 pound of cottonseed cake per head daily with free access to salt. During the experiment all were fed in drylot, except Lot 1, which was fed out on dry bluestem pasture. All lots had free access to a mineral mixture (bonemeal and salt) and salt during the winter. The different lots received the following rations from December 22,1951. to May 2, 1952: Lot 1-Bluestem pasture and 2 pounds cottonseed cake per head daily; Lot 2-Sorghum silage and 1 pound cottonseed cake per head daily; Lot 3-Prairio hay and 1 pound cottonseed cake per head daily; Lot 4-Prairie hay, 2 pounds milo grain, and 1 pound cottonseed cake per head daily; Lot 5-Prairie hay, 4 pounds milo grain, and 1 pound cottonseed cake per head daily. All lots were grazed on bluestem pasture a full season in 1952 and sold as feeder or stocker yearlings in the fall. A feedstuff analysis of the feeds used in the test may be found in the back of this publication. The final weights are full weights and should be shrunk at least 3 percent for a more complete picture of steer gain.
Keywords: Beef; Gain; Bluestem pasture; Yearlings